Structure and function of human XPR1 in phosphate export - Long Chen; Jin He; Mingxing Wang; Ji She (Nature Communications)
Abstract Xenotropic and polytropic retrovirus receptor 1 (XPR1) functions as a phosphate exporter and is pivotal in maintaining human phosphate homeostasis. It has been identified as a causative gene for primary familial brain calcification. Here we present the cryogenic electron microscopy (cryo-EM) structure of human XPR1 (HsXPR1). HsXPR1 exhibits a dimeric structure in which only TM1 directly constitutes the dimer interface of the transmembrane domain. Each HsXPR1 subunit can be divided spatially into a core domain and a scaffold domain. The core domain of HsXPR1 forms a pore-like structure, along which two phosphate-binding sites enriched with positively charged residues are identified. Mutations of key residues at either site substantially diminish the transport activity of HsXPR1. Phosphate binding at the central site may trigger a conformational change at TM9, leading to the opening of the extracellular gate. In addition, our structural analysis reveals a new conformational state of HsXPR1 in which the cytoplasmic SPX domains form a V-shaped structure. Altogether, our results elucidate the overall architecture of HsXPR1 and shed light on XPR1-mediated phosphate export.